Contribution of APOBEC3G/F activity to the development of low-abundance drug-resistant human immunodeficiency virus type 1 variants. (February 2016) - Noguera-Julian, M.; Cozzi-Lepri, A.; Di Giallonardo, F.; Schuurman, R.; Däumer, M.; Aitken, S.; Ceccherini-Silberstein, F.; D'Arminio Monforte, A.; Geretti, A.M.; Booth, C.L.; Kaiser, R.; Michalik, C.; et al.
Abstract: Plasma drug-resistant minority human immunodeficiency virus type 1 variants (DRMVs) increase the risk of virological failure to first-line non-nucleoside reverse transcriptase inhibitor antiretroviral therapy (ART). The origin of DRMVs in ART-naive patients, however, remains unclear. In a large pan-European case–control study investigating the clinical relevance of pre-existing DRMVs using 454 pyrosequencing, the six most prevalent plasma DRMVs detected corresponded to G-to-A nucleotide mutations (V90I, V106I, V108I, E138K, M184I and M230I). Here, we evaluated if such DRMVs could have emerged from apolipoprotein B mRNA editing enzyme, catalytic polypeptide 3G/F (APOBEC3G/F) activity. Out of 236 ART-naive subjects evaluated, APOBEC3G/F hypermutation signatures were detected in plasma viruses of 14 (5.9%) individuals. Samples with minority E138K, M184I, and M230I mutations, but not those with V90I, V106I or V108I, were significantly associated with APOBEC3G/F activity (Fisher's P <  0.005), defined as the presence of > 0.5% of sample sequences with an APOBEC3G/F signature. Mutations E138K, M184I and M230I co-occurred in the same sequence as APOBEC3G/F signatures in 3/9 (33%), 5/11 (45%) and 4/8 (50%) of samples, respectively; such linkage was not found for V90I, V106I or V108I. In-frame STOP codons were observed in 1.5% of all clonal sequences; 14.8% of them co-occurred with APOBEC3G/F signatures. APOBEC3G/F-associated E138K, M184I and M230I appeared within clonal sequences containing in-frame STOP codons in 2/3 (66%), 5/5 (100%) and 4/4 (100%) of the samples. In a re-analysis of the parent case control study, the presence of APOBEC3G/F signatures was not associated with virological failure. In conclusion, the contribution of APOBEC3G/F editing to the development of DRMVs is very limited and does not affect the efficacy of non-nucleoside reverse transcriptase inhibitor ART.